YouTube as a Source of Information in Trauma Management for ATLS (10th Edition) Guidelines - Merve Yazla; Seyma Handan Akyon; Esin Aslı Aybayar; Seyda Gedikaslan; Lukasz Szarpak; Omer Faruk Turan; Jacek Smereka; Mustafa Ekici; Abdullah Osman Kocak; Burak Katipoglu (Emergency Medicine International)
Conclusion: YouTube is an information source about trauma management that contains videos of varying quality and has a broad audience. Official institutions and healthcare professionals should be aware of this evolving technology and publish up-to-date, accurate content to increase awareness about trauma management and help patients distinguish helpful information from misleading content.